2023
DOI: 10.1029/2022gl101953
|View full text |Cite
|
Sign up to set email alerts
|

Solar Cycle and Long‐Term Trends in the Observed Peak of the Meteor Altitude Distributions by Meteor Radars

Abstract: There has been an increasing interest in how our whole atmosphere is changing ever since modeling work by Roble and Dickinson (1989) demonstrated the global mean mesospheric temperatures would cool by ∼10 K under a doubled-CO 2 emission scenario. While it is commonly understood that greenhouse gases (GHGs) act as radiative heaters in Earth's atmosphere, these same gases act as net radiative coolers in the mesosphere and lower thermosphere (MLT) region, as re-emitted heat energy is simply lost to space due to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Like the WACCM results, we also found no significant change in RMS width. We note with interest that a very recent report based on long-term meteor radar observations at 12 stations also showed decreasing meteor ablation altitude and positive correlation with solar activity (Dawkins et al, 2023).…”
Section: Discussionmentioning
confidence: 53%
“…Like the WACCM results, we also found no significant change in RMS width. We note with interest that a very recent report based on long-term meteor radar observations at 12 stations also showed decreasing meteor ablation altitude and positive correlation with solar activity (Dawkins et al, 2023).…”
Section: Discussionmentioning
confidence: 53%
“…The average altitude of the meteor echoes in each month (Figure S1 in Supporting Information S1) is consistent between ∼88 and ∼91 km throughout the observational period. Further it is in phase with the 11-year SC as revealed in a recent study of the long-term variability in the heights of meteor echoes (Dawkins et al, 2023), that investigated data from 12 meteor radars (including the Esrange radar used in this study) and showed both linear and 11-year variations in peak meteor height. The peak heights decreased at all sites and a positive correlation with solar activity was observed at most sites; however, at high latitudes an anticorrelation was observed.…”
Section: Meteor Radar Observations Over Esrangementioning
confidence: 59%
“…For example, ref. [147] looked at ~20-year data sets from 12 widely distributed meteor radars and found decreasing altitudes at all locations, and a positive correlation in peak height with solar activity.…”
Section: Measuring Density and Temperature: Anomalous Diffusionmentioning
confidence: 99%